Análise integrada dos aspectos geoambientais e da dinâmica costeira de médio e curto período da planície litorânea entre as Praias do Futuro e Porto das Dunas, Ceará, Brasil - Marino, Márcia Thelma Rios Donato (2014)
This research analyzes the geo-environmental aspects in an integrated manner and the coastal dynamics of short to medium duration of the coastal plain between the Porto das Dunas Beach and Praia do Futuro Beach, East coast of Ceará state. It is based on multitemporal analysis of shoreline variation and morphological changes. This work applied the geoprocessing reconciled to geoenvironmental characteristics, morphodynamics, hydrodynamics, aeolian processes, anthropogenic actions and assessment indices of vulnerability to erosion. The area of investigation stretches 15 km of coastline represented by 3 sectors: 1-Porto das Dunas Beach; 2-Abreulândia (COFECO) Beach and Sabiaguaba Beach; and 3- Caça e Pesca Beach and Praia do Futuro Beach, in addition to the mouths of the Pacoti River and Cocó River. Methodologically, it wasguided by activities of staff, field, laboratory and integrated analysis of the data. Seasonal monitoring was elaborated during a year (08/10 to 08/11). Geologically the area is comprised of two geological domains: basal unit and the coastal plain, both of which influence the coastal dynamics of the beaches of interest-more specifically, those related to weather conditions. The climate is rainy and tropical, semi-arid, and features strong annual rainfall irregularity that characterize two distinct seasons: one with prolonged drought and another with short rainfall. The data wave modal reveal the predominance of sliding type, beaches with soft and low reliefs declivities. The height of the waves in the surf zone presented average value of 1,1m, ranging from 0,9 m to 1,2m. The wave periods follow a seasonal pattern, with smaller waves in the dry season and larger ones in rainy season (maximum of 15,9s and minimum of 6,1s). The morphodynamic stage is dissipative in Sector 1, in Sector 2 ranges from dissipative to intermediary and, sometimes, reflective. In Sector 3 it predominates the dissipative to intermediary stages with the largest extensions of beach profiles. The sedimentary balance confirms a state seeking a balance between depositional and erosional processes, however with erosional trend for Sectors 1 and 2, and depositional trend for Sector 3. This corroborates with the sediment volumes and with the coastline variation. The rates of advance and retreat of the shoreline were obtained using the Digital Shoreline Analysis System, software for ArcGIS 10.0, integrating georeferenced data, between 1972 and 2010. From Porto das Dunas Beach to the left margin of Pacoti River it was set up an erosion stage on an average of – 3,53m/year and -17.65m in 5 years. Between the mouth of the Pacoti River and Abreulândia Beach erosion rates were observed, average of -0,31m/year and -2.18m in a period of 7 years. The area from Abreulândia Beach to the mouth of the Cocó River showed erosional average of -0.07m/year, -2,59m in a period of 38 years. This evidences stability in this sector, probably due to discontinuous cord beachrocks parallel to the coast. Praia do Futuro Beach has a strong progradational average of +1.43m/year, +54.33m in a period of 38 years. The analysis of textural variation of beach sediments noted the predominance of the sandy fraction over the 15 km of beaches with medium sand, moderately selected, with finer fractions on the beaches of the far NW and the thicker on the central portions. The grain size characteristics of this coastline is strongly conditioned by the influence of hydrodynamic, wind, and weather agents, associated with the type, orientation, and location of the beach as well as the proximity and type of sediment source area. The beach morphodynamic profiles are associated with weather seasonality, winter profiles during periods of transition and drought. Moreover, summer profiles are observed in the rainy season. The distribution of sediments along the profiles was recorded in the rainy season showing a predominance of coarse in the outlying areas of the coastline and the finest in subaqueous region. In the dry season the effect is inverse. Three facts are highlighted for the speeds of the winds: development of a vertical upward gradient, certain conformity of behavior of curves drawn in different heights, and speeds in the backshore zone. The Pacoti River and the Cocó River showed narrowing in the mouth and erosion on adjacent beach tracks. Furthermore, it was observed in the mouths a relationship directly proportional between the beach range and the underwater deposits, suggesting that these deposits act as sediment suppliers to the beach range. The factors analyzed have led to the evolution of the coast and were relevant to assessing the degree of vulnerability to coastal erosion. Resulting from this process was a very high degree to the Sector 1, high to low degree to the Sector 2 and low to medium degree to the Sector 3, related to the features and types of use. The urbanization process taking place in the area is accelerated and unplanned. For example, it does not take into consideration the characteristics and weaknesses of ecosystems, such as the occupation of the by-pass areas. This latter has a direct influence on natural seasonality of removal and deposition of sandy sediments, resulting in the indentation of the coastline, due to the reduction in the contribution of sediments. Stricter supervision is recommended, and implementation of a monitoring programme and a spatial planning programme in this area are essential for the coastal dynamic balance.